Kundrelationer : mellan Setragroup AB och bygghandeln - Bäckman, Jakob (SLU/Dept. of Forest Products, 2008)
This study is made in cooperation with Setragroup AB. Setra is Sweden's biggest sawmilling company with a turnover of almost 6 billion SEK. 45% of the produced volume goes to the Swedish market where the customers are the DIY-sector and industrial customers. Setra as well as the other Swedish sawmilling companies operate in a very competitive environment. The customers demand on the products and the distribution of them increases and tend to be more sophisticated with a simultaneously growing competition from low cost countries. Under these circumstances it becomes very important for the companies to satisfy their customers' needs in a successful way.